Surgical treatment of a periapical lesion in a patient with a history of alendronate-associated osteonecrosis (Research, Society and Development, 2026)
Medication-related osteonecrosis of the jaws is a clinical complication associated with the use of antiresorptive agents, especially alendronate, which may impair bone remodeling and tissue repair, increasing the risk of complications after procedures. The aim of this study is to report a clinical case of surgical treatment of a periapical lesion in a patient with a history of medication-related osteonecrosis of the jaws associated with alendronate use, highlighting the therapeutic approach adopted and the clinical outcomes obtained. A 62-year-old female patient, with a history of alendronate use for more than 10 years, discontinued two years earlier after a previous episode of osteonecrosis, presented with a persistent periapical lesion associated with teeth 31 and 32. Clinical and tomographic evaluation confirmed the diagnosis, and laboratory tests were within normal limits. Surgical treatment consisted of lesion curettage, apicectomy without retrograde filling, use of platelet-rich fibrin, and low-level laser therapy, associated with preoperative antibiotic therapy. Postoperative follow-up at 10 and 30 days showed adequate tissue healing and favorable progression of bone repair, with no signs of infection, recurrence, or osteonecrosis. Parendodontic surgery may be a viable and safe alternative in patients with a history of prolonged bisphosphonate use and previous osteonecrosis, provided that careful case selection is performed, minimally invasive techniques are adopted, and adjuvant therapies are used to promote healing and reduce the risk of complications.